Introducing the ten recitations and explaining the impact of the recitations on interpretation - Mustafa Najm Abdullah,; Farman Ismail Ibrahim, (Islamic Sciences Journal, 2024)
ABSTRACT This research is concerned with Qur’anic readings and their impact on interpretation by talking about Qur’anic readings: their definition, the emergence of the science of readings, the reasons for differences in reciters in them, and the impact of Qur’anic readings in interpretation. The research included an applied study on various models of the ten different aspects of frequent recitations according to the standards considered in Judging the readings and explaining their impact on interpretation, through: 1-Writing the Qur’anic verse in question in its entirety and in a form based on the narration of Hafs on the authority of Asim. 2-Introducing the ten reciters and their narrators 3-Explaining the different readings in the verse by referring to famous books of readings. 4-Explaining the linguistic meaning of the readings if there is a meaning that is not explained by referring to language books and dictionaries. 5-Interpreting the verse being read in a comprehensive manner, while adhering to the controls set by the scholars of interpretation according to the praiseworthy and permissible opinion, using ancient and modern books of interpretation. 6 - Explaining the interpretive relationship between the Qur’anic readings and explaining the meanings that each reading adds to the others.